Evaluasi sistem manajemen terhadap kualitas pengurus koperasi - Ukiki; Yunia Misdalena (ARKA INSTITUTE, 2022)
The purpose of this study is to evaluate the effect of management information systems on the success of cooperatives based on the quality of members. In addition, this research can also be used as material for evaluation and consideration for future cooperatives. In this study used qualitative with descriptive analysis. The collection technique is carried out in a combined manner, the data analysis is inductive, and the results of qualitative research emphasize the meaning of generalizations. Based on the results of the research that has been done, the conclusion that can be drawn in this study is that the participation of members in KUD Setia Manggung can increase the success of their cooperatives based on maximizing Human Resources, capital contributions, maximizing cooperative services, supervising cooperatives, and also structured payments on each transaction carried out. voted by member users/owners at KUD Setia Manggung.